2019
DOI: 10.1177/0268355519856756
|View full text |Cite
|
Sign up to set email alerts
|

Granuloma formation following cyanoacrylate glue injection in peripheral veins and arteriovenous malformation

Abstract: Background Cyanoacrylate adhesive closure is a technically simple alternative to endothermal ablation of peripheral veins. N-butyl cyanoacrylate is delivered via catheters or by percutaneous injection resulting in occlusion of target veins. The local tissue reaction or the systemic immune response that may follow have not been characterised. Aim To characterise the late local tissue reaction to N-butyl cyanoacrylate glue injected in peripheral vessels. Methods Biopsies were obtained from two patients. In patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
0
35
0
2
Order By: Relevance
“…We would suggest a potential mechanism may be a chronic immunological reaction to cyanoacrylate with subsequent damage to the vessel wall; this is supported by emerging clinical and preclinical reports of immunological reactions to cyanoacrylate treatment. [9][10][11] An alternative mechanism is that during compression after glue installation, as per the manufacturer's instructions for use, glue may be compressed into a very small tributary leading to its rupture, extravasation and subsequent foreign body reaction. We would therefore suggest that such compression should be light and applied with great care.…”
Section: Discussionmentioning
confidence: 99%
“…We would suggest a potential mechanism may be a chronic immunological reaction to cyanoacrylate with subsequent damage to the vessel wall; this is supported by emerging clinical and preclinical reports of immunological reactions to cyanoacrylate treatment. [9][10][11] An alternative mechanism is that during compression after glue installation, as per the manufacturer's instructions for use, glue may be compressed into a very small tributary leading to its rupture, extravasation and subsequent foreign body reaction. We would therefore suggest that such compression should be light and applied with great care.…”
Section: Discussionmentioning
confidence: 99%
“…21 The second is an Australian study where serial biopsies were taken at one week, six weeks and one year after Venablock TM treatment of peripheral veins. 22 The Russian study reported mast cell degranulation in the peri-vascular space within 10 min of exposure to glue. 21 In AVM studies, acute inflammation consisting mainly of polymorphonuclear cells was observed with foci of intramural haemorrhage within 24-48 h of n-BCA injection.…”
Section: Tissue Response To Cyanoacrylatementioning
confidence: 99%
“…No histiocytes or granulomas were present at this stage. 22 The AVM studies showed that by weeks 2-3, there was a granulocytic infiltration of vessel walls and the peri-vascular tissue. The vessel wall showed patchy loss of intima, medial necrosis as well as early foreign body giant cell formation and round-cell infiltration.…”
Section: Tissue Response To Cyanoacrylatementioning
confidence: 99%
See 2 more Smart Citations